Reevaluating the CD8 T-Cell Response to Herpes Simplex Virus Type 1: Involvement of CD8 T Cells Reactive to Subdominant Epitopes - Sheridan, Brian S. (American Society for Microbiology (ASM), 2009)
In C57BL/6 (B6) mice, most herpes simplex virus (HSV)-specific CD8 T cells recognize a strongly immunodominant epitope on glycoprotein B (gB(498)) and can inhibit HSV type 1 (HSV-1) reactivation from latency in trigeminal ganglia (TG). However, half of the CD8 T cells retained in latently infected TG of B6 mice are not gB(498) specific and have been largely ignored. The following observations from our current study indicate that these gB(498)-nonspecific CD8 T cells are HSV specific and may contribute to the control of HSV-1 latency. First, following corneal infection, OVA(257)-specific OT-1 CD8 T cells do not infiltrate the infected TG unless mice are simultaneously immunized with OVA(257) peptide, and then they are not retained. Second, 30% of CD8 T cells in acutely infected TG that produce gamma interferon in response to HSV-1 stimulation directly ex vivo are gB(498) nonspecific, and these cells maintain an activation phenotype during viral latency. Finally, gB(498)-nonspecific CD8 T cells are expanded in ex vivo cultures of latently infected TG and inhibit HSV-1 reactivation from latency in the absence of gB(498)-specific CD8 T cells. We conclude that many of the CD8 T cells that infiltrate and are retained in infected TG are HSV specific and potentially contribute to maintenance of HSV-1 latency. Identification of the viral proteins recognized by these cells will contribute to a better understanding of the dynamics of HSV-1 latency.